An analysis of the relatioship between spiritual marketing and consumer loyalty in culinary products based on location - Arif, Chairul (Institute for Advanced Social, Science, and Sustainable Future, 2025)
Background: In today's global era, new lifestyles have emerged, including an increasing public interest in traveling. When traveling, Indonesians have a tradition of purchasing local souvenirs, such as food or handicrafts. Spiritual marketing is an ethics- and honesty-based strategy, particularly in Sharia-compliant businesses, emphasizing sympathetic attitudes and good relationships with consumers. Methods: This investigation utilizes Multiple linear regression approach with the Accidental sampling method, involving 140 respondents. Findings: The Modified R-Square (Adjusted R²) Value test yields a value of 0.422, suggesting that 42.2% of consumer loyalty is influenced by spiritual price, spiritual product, spiritual place and spiritual promotion while the remaining 57.8% is shaped by other factors. The F-test results indicate that the calculated F-value (26.379) exceeds the F-table value (2.43), with a significance level of 0.000 < 0.05. This leads to the rejection of H₀ and acceptance of Hₐ, confirming that these four spiritual variables collectively have a significant impact on consumer loyalty toward risol gogo products.The T-test results further reveal that each individual variable exerts a strong and meaningful impact on consumer loyalty. Conclusion: by spiritual price, spiritual product, spiritual place and spiritual promotion play a crucial role in shaping consumer loyalty. Novelty/Originality of this article: This research provides a fresh perspective by examining the intricate relationship between traditional marketing and spiritual marketing, an area that remains underexplored in previous studies.